(untitled) - Moss, Kevin L (Boston, MA, 2006)
The digital nature photographer does more than just take pictures. He is part adventurer, part traveler, and part nature and wildlife observer - on top of being a skilled photographer. "Digital Nature Photography and Adobe® Photoshop®" addresses the unique challenges and needs of the digital nature photographer, combining an advanced guide to shooting and composition with information on editing and processing nature and landscape photos using Adobe Photoshop. Divided into two parts, the first half of the book provides in-depth information on the essential computer equipment, field gear, and techniques needed to shoot digital nature photography, whereas the second half details workflow and advanced editing techniques. Discover the advantages of digital over film for nature photography and how to choose the right camera and accessories. Learn what hardware, software, special tools, and storage devices work best. And outfit yourself and your equipment for the wilderness with the proper tripods, camera bags, clothing, and more. Then get ready to master the essential skills for shooting landscapes, photographing wildlife, creating abstract and macro shots, and even using Camera Raw for nature photography. All skills are taught using step-by-step tutorials enhanced by stunning, full-color examples of digital nature photography. Once you've captured your incredible nature photographs, get acquainted with Adobe Photoshop as you learn how to use the software to edit and finish your photos. Color management, layers, tonal and color corrections, and simple editing tasks are all covered. This comprehensive guide even shows you how to create special effects using Photoshop filters and how to convert color images into spectacular black-and-white photographs.
Keywords: Nature photography,Image processing,Ảnh thiên nhiên kỹ thuật số,Xử lý ảnh kỹ thuật số; Digital techniques